The formation of the creative competence of future teachers of primary classes in the training - Онищенко, І. В. (Educational Dimension, 2012)
Onishchenko I. The formation of the creative competence of future teachers of primary classes in the training. The article considers the problem of formation of the creative competence of the future primary school teachers, determines the essence, structure, ways and conditions of formation of the creative competence of future primary school teachers in the process of training.